2021
DOI: 10.7759/cureus.13301
|View full text |Cite
|
Sign up to set email alerts
|

Levofloxacin-Induced Acute Pancreatitis

Abstract: Drug-induced pancreatitis is a rare entity accounting for less than 2% of acute pancreatitis (AP). Quinolones are commonly used antimicrobials with occasional reports of pancreatitis. We present the case of a 74-year-old man who was diagnosed with acute cystitis five days before hospital admission and was treated with levofloxacin (LVF). Two days after initiating LVF he experienced fever, severe abdominal pain, and nausea. The initial assessment revealed leukocytosis, elevated C-reactive protein, and a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…He had taken levofloxacin for acute cystitis for the last 2 days. 9 Rekhi et al 10 reported a case of levofloxacin-induced acute pancreatitis in a young patient. She was commenced on levofloxacin due to pneumonitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…He had taken levofloxacin for acute cystitis for the last 2 days. 9 Rekhi et al 10 reported a case of levofloxacin-induced acute pancreatitis in a young patient. She was commenced on levofloxacin due to pneumonitis.…”
Section: Discussionmentioning
confidence: 99%
“…highlighted a case of acute pancreatitis in an old male induced by levofloxacin. He had taken levofloxacin for acute cystitis for the last 2 days 9 . Rekhi et al 10 .…”
Section: Discussionmentioning
confidence: 99%